Identification of Factors Associated With Delayed Treatment of Obstetric Hypertensive Emergencies. Issue 1 (January 2021) - Kantorowska, Agata; Heiselman, Cassandra J.; Halpern, Tara A.; Akerman, Meredith B.; Elsayad, Ashley; Muscat, Jolene C.; Sicuranza, Genevieve B.; Vintzileos, Anthony M.; Heo, Hye J.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223:250.e1–250.e11) Obstetric hypertensive emergency is a serious hypertensive disorder that can complicate pregnancy and lead to maternal death. It is defined as acute-onset and severe high blood pressure (BP) that lasts for 15 minutes or longer.